Developing and using a School Menu Healthiness Assessment Tool to analyse school food provision in Wales - Gilmour, Alice; Fairchild, Ruth (Public health nutrition, 2025)
To design and develop a new, innovative and valid School Menu Healthiness Assessment Tool that is suitable for the quantitative and qualitative analysis of school food and drink provision. Second, to analyse primary and secondary school menus and price lists pan-Wales to ascertain their healthiness and whether free school meal (FSM) eligible pupils can afford to access healthy, nutritious food across the school day. Codable items and categories of school food and drink provision were operationalised before the tool underwent iterative development and testing. Then, cross-sectional content analysis of publicly available documents detailing school food provision (i.e. menus and price lists) was done. Primary and secondary schools in Wales, UK. In total, 82 canteen menus were sourced online. This comprised local authority catering for primary ( 22) and secondary ( 19) schools and school-organised catering for primary ( 5) and secondary ( 36) schools. Intercoder reliability testing found high agreeability between coders, demonstrating that the tool and data interpretation are reproducible and trustworthy. The FSM allowance is not wholly sufficient for all secondary school pupils to purchase a healthy meal from the school canteen. Moreover, the tool identified that oily fish and wholegrain provision were lacking across many menus. A valuable tool was created, useful for researchers and other health professionals (i.e. dietitians) who are required to analyse the healthiness of school food provision in line with the latest nutritional requirements. This study provides insight into the current school food and drink landscape pan-Wales.